Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N.; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M.; Hunter, Jill V.; Atik, Mehmed M.; et al. (Neuron (Cambridge, Mass.), 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations. [Display omitted] •Rare variant analysis (SNV and CNV) in a large cohort with brain malformation•Gene discovery facilitated by neuroimaging and in silico analysis•Mutations in PRUNE in families with abnormal fore and hindbrain development Karaca et al. underscore the power of a genomic approach combined with neuroimaging and in silico studies in human subjects with cortical abnormalities. This allows for further understanding of genetic networks underlying specific types of cortical development malformations.